Self-management education of children with asthma: AIR WISE. - McNabb, W L (1985)
This study was conducted to test the efficacy of AIR WISE, an individually administered asthma self-management program. Subjects were paired and randomly assigned to either an experimental group (N = 7) or a control group (N = 7). The frequency of experimental group emergency visits, analyzed over a 12-month posttreatment period, was substantially less than those of the control group, supporting the hypothesis that AIR WISE is effective in high-utilizer children through improved self-management.